2019
DOI: 10.1007/s00592-019-01454-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequent physical activity is associated with reduced risk of severe diabetic retinopathy in type 1 diabetes

Abstract: Aims The aim of this study was to investigate whether leisure-time physical activity (LTPA) is associated with the development of severe diabetic retinopathy in individuals with type 1 diabetes. Methods Prospective observational analysis as part of the Finnish diabetic nephropathy (FinnDiane) Study with a mean follow-up time of 10.7 years was performed. A total of 1612 individuals with type 1 diabetes were recruited, and LTPA was assessed at baseline using a validated self-report questionnaire. Severe diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
0
12
1
1
Order By: Relevance
“…In a recent meta-analysis by Ren et al, authors revealed that physical activity has a slight protective association with retinopathy in patients with diabetes, and the impact was more pronounced on vision-threatening retinopathies (109). The amount of exercise or its components (time or intensity of each session) were not linked with severe retinopathy (110).…”
Section: Exercise Recommendations In Patients With Diabetes-related Cardiovascular Complicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis by Ren et al, authors revealed that physical activity has a slight protective association with retinopathy in patients with diabetes, and the impact was more pronounced on vision-threatening retinopathies (109). The amount of exercise or its components (time or intensity of each session) were not linked with severe retinopathy (110).…”
Section: Exercise Recommendations In Patients With Diabetes-related Cardiovascular Complicationmentioning
confidence: 99%
“…However, due to the risk of vitreous hemorrhage and retinal detachment in patients with unstable diabetic retinopathy, special exercise cautions are needed (32). In conclusion, the proper exercise program should be tailored for patients with diabetic retinopathy, especially in the mild and stable forms (26,32,73,109,110).…”
Section: Exercise Recommendation In Patients With Diabetic Retinopathymentioning
confidence: 99%
“…In addition, exercise also lowers the risk of a variety of chronic conditions, such as type 2 diabetes [93], CVD [95], hypertension [96], and dementia [97], while slowing age-related decline in physical function [98]. In those with T1D in particular, exercise and physical activity are associated with not only greater longevity [99,100], but also a decrease in the frequency and severity of diabetes-related complications [101][102][103].…”
Section: Exercise and T1dmentioning
confidence: 99%
“…Пациентам с пролиферативной или тяжелой непролиферативной диабетической ретинопатией противопоказаны силовые тренировки и интенсивные упражнения или соревнования на выносливость из-за риска спровоцировать кровоизлияние в стекловидное тело или отслойку сетчатки [38]; гемофтальм, отслойка сетчатки, первые полгода после лазеркоагуляции сетчатки являются ограничениями для любых видов физических упражнений [39].…”
Section: противопоказания и меры предосторожности при выполнении упраunclassified